Analysis of complete integrability of a system inverse to the nonlinear Benney-Kaup system - Drobotskaya, I. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We study a system inverse to the nonlinear dynamical Benney-Kaup system. For this system, we prove the existence of an infinite hierarchy of functionally independent and involution conservation laws; a pair of implicative and Noetherian operators is constructed which enables one to write the system in a bi-Hamiltonian form; we also present the explicit form of the Lax operator.